Density dependence, prey accessibility and prey depletion by fisheries drive Peruvian seabird population dynamics. Issue 7 (4th December 2017) - Barbraud, Christophe; Bertrand, Arnaud; Bouchón, Marilú; Chaigneau, Alexis; Delord, Karine; Demarcq, Hervé; Gimenez, Olivier; Torero, Mariano Gutiérrez; Gutiérrez, Dimitri; Oliveros‐Ramos, Ricardo; Passuni, Giannina; Tremblay, Yann; et al.
Abstract : In marine ecosystems top predator populations are shaped by environmental factors affecting their prey abundance. Coupling top predators' population studies with independent records of prey abundance suggests that prey fluctuations affect fecundity parameters and abundance of their predators. However, prey may be abundant but inaccessible to their predators and a major challenge is to determine the relative importance of prey accessibility in shaping seabird populations. In addition, disentangling the effects of prey abundance and accessibility from the effects of prey removal by fisheries, while accounting for density dependence, remains challenging for marine top predators. Here, we investigate how climate, population density, and the accessibility and removal of prey (the Peruvian anchovy Engraulis ringens ) by fisheries influence the population dynamics of the largest sedentary seabird community (≈ 4 million individuals belonging to guanay cormorant Phalacrocorax bougainvillii, Peruvian booby Sula variegata and Peruvian pelican Pelecanus thagus ) of the northern Humboldt Current System over the past half‐century. Using Gompertz state–space models we found strong evidence for density dependence in abundance for the three seabird species. After accounting for density dependence, sea surface temperature, prey accessibility (defined by the depth of the upper limit of the subsurface oxygen minimum zone) and prey removal by fisheries were retained as the best predictors of annual population size across species. These factors affected seabird abundance the current year and with year lags, suggesting effects on several demographic parameters including breeding propensity and adult survival. These findings highlight the effects of prey accessibility and fishery removals on seabird populations in marine ecosystems. This will help refine management objectives of marine ecosystems in order to ensure sufficient biomass of forage fish to avoid constraining seabird population dynamics, while taking into account of the effects of environmental variability.